STUDI METODE CRAMER DAN METODE INVERS MATRIK PADA PERSOALAN RANGKAIAN LISTRIK - Ilmi, Ulul; Faroh, Rifky Aisyatul; Hanifah, Ayu Ismi; Mukhoyyaroh, Nur Indah; Masruroh (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2023)
In the world of engineering, one example of using a matrix is to find a solution to a system of linear equations (SLE). In the scientific field that studies electrical circuits, it is not uncommon to use matrices to calculate the quantities or values in an electric circuit. To make it easier to find these values, an operation process based on the Cramer and inverse methods based on Matlab is used so that finally the values contained in the electrical circuit are obtained. These values are electric current and electric voltage. In this study, it can be concluded that the use of the Matlab-based matrix inverse method is better in terms of the accuracy of the research results, when compared to the manual use of the Cramer method, which has an accuracy difference of 0.0006%. For the calculation of the current variable i3. and 0.81% for the calculation of the electric voltage variable at node AB.